Antioxidant and antiproliferative activities of non-edible parts of selected tropical fruits - Warangkana Chunglok,; Tanyarath Utaipan,; Nathnarin Somchit,; Monthon Lertcanawanichakul,; Yuttana Sudjaroen, (Universiti Kebangsaan Malaysia, 2014)
It is of interest that seeds and pericarps of tropical fruits contain phytochemicals being the components of various biological activities for beneficial health effects. This study was aimed to evaluate antioxidant and anticancer activities of the methanolic extracts from seeds and pericarps of three selected tropical fruits including Rambutan (Nephelium lappaceum L.), Litchi (Litchi chinensis Sonn.) and Tamarind (Tamarindus indica L.). Total phenolic content was determined by using the Folin-Ciocalteu method. Antioxidant capacity was evaluated based on the ability of the fruit extracts to scavenge ABTS and DPPH radicals. MTT reduction assay and Annexin V-FITC/PI staining were carried out for cytotoxicity and apoptosis induction, respectively. Total phenolic contents of the seeds and pericarps of the tropical fruits ranged from 104.60 to 501.95 mg/g DW. All extracts were found to have significant antioxidant activities. Among them, tamarind seed extract contained the highest total phenolic contents and possessed the highest antioxidant capacities. Tamarind seed extract showed the highest cytotoxicity to human mouth carcinoma (CLS-354) cells and had no toxicity to PBMCs. Staining with annexin V-FITC/PI showed that this apoptosis occurred early in this cell type with 10.0% of the cells undergoing apoptosis. Tamarind seed extract might have potential anticancer activity which could be attributed, in part, to selectively inhibit the growth of CLS-354 cells and induce apoptosis. This research finding would be valuable information to identify major constituents of the extracts and mechanisms underlying anticancer activity which could be attributed to dietary health supplements or cancer chemoprevention from fruits.